2014
DOI: 10.1007/s11033-014-3792-3
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and association analysis of GmCYP78A10 gene with seed size/weight and pod number in soybean

Abstract: Seed-size/weight traits, controlled by multiple genes in soybean, play an important role in determining seed yield. However, the molecular mechanisms controlling the seed size and weight in soybean remain unclear. In Arabidopsis, P450/CYP78A gene family has been proved extremely relevant to seed size (such as AtCYP78A5, AtCYP78A6 and AtCYP78A9). We found that a soybean GmCYP78A10 gene underwent artificial selection during soybean breeding. The GmCYP78A10a allele mainly distributed in wild soybean (Glycine soja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
76
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 39 publications
0
76
2
Order By: Relevance
“…In our study, a number of ubiquitin-mediated proteolysis candidate genes were found to be significantly enriched in seed coat at the early seed maturation stage (S3-1) in V1. Cytochrome P450 family genes have been reported to positively regulate seed yield in rice and soybean (Wang et al , 2015; Yang et al , 2013). In our study, several candidate cytochrome P450 family genes exhibited high expression levels in the seed coat of the large seed cultivar, V1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, a number of ubiquitin-mediated proteolysis candidate genes were found to be significantly enriched in seed coat at the early seed maturation stage (S3-1) in V1. Cytochrome P450 family genes have been reported to positively regulate seed yield in rice and soybean (Wang et al , 2015; Yang et al , 2013). In our study, several candidate cytochrome P450 family genes exhibited high expression levels in the seed coat of the large seed cultivar, V1.…”
Section: Resultsmentioning
confidence: 99%
“…A cytochrome P450 family gene, GmCYP78A5 ( Glyma.05G019200 ), was found to be involved in soybean seed size and pod number by association analysis (Wang et al , 2015). This gene was more highly expressed in V1S2 samples compared with V2S2 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is very little published information regarding the genes responsible for NPS‐related traits. However, ln was confirmed to be related to NFSP (Jeong et al., ), GmCYP78A10 is related to NPPP (Wang et al., ), and a pentatricopeptide repeat ( PPR ) gene is related to NPPP in chickpea (Shouvik et al., ). Additionally, the observations of many studies have suggested that the development of the ovule, embryo, pollen, stamen and flower considerably influences pod and seed set (Ali & Rocha, ; Endo & Ohashi, ; Jiang et al., ; Kurdyukov, Song, Sheahan, & Rose, ; Mukhtar & Coyne, ; Qi et al.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, gibberellins (GAs) were shown to play an important role, because lines overexpressing the rate-limiting GA biosynthetic enzyme GA20-OXIDASE had larger leaves due to an increase in the leaf elongation rate (LER) and the number of dividing cells13. More recently, a cytochrome P450 CYP78A, named KLUH, was shown to regulate vegetative and reproductive organ growth across plant species by promoting cell proliferation likely through generation of a mobile growth-promoting signal161718192021. In rice, PLASTOCHRON1 ( PLA1 ) that belongs to the same class of CYP78A as KLUH affects the timing of leaf initiation and vegetative growth22.…”
mentioning
confidence: 99%